2000
DOI: 10.1017/s1355838200001242
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of eukaryotic translation termination by selected RNAs

Abstract: Using selection-amplification, we have isolated RNAs with affinity for translation termination factors eRF1 and eRF1•eRF3 complex. Individual RNAs not only bind, but inhibit eRF1-mediated release of a model nascent chain from eukaryotic ribosomes. There is also significant but weaker inhibition of eRF1-stimulated eRF3 GTPase and eRF3 stimulation of eRF1 release activity. These latter selected RNAs therefore hinder eRF1•eRF3 interactions. Finally, four RNA inhibitors of release suppress a UAG stop codon in mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Rather, our results suggest that eukaryotic release factors, eRF1/eRF3, terminate translation more efficiently at the opal and ochre codons as opposed to the amber codons. Consistent with this hypothesis, addition of an RNA aptamer previously shown to inhibit eRF1/eRF3 (Carnes et al 2000) improved NBD-[ 14 C]Cys incorporation efficiency by twofold at the opal codon and fourfold at the ochre codon (Fig. 4B).…”
Section: Incorporation Of Nbd-labeled Cys Using Cys-derived Suppressosupporting
confidence: 77%
See 1 more Smart Citation
“…Rather, our results suggest that eukaryotic release factors, eRF1/eRF3, terminate translation more efficiently at the opal and ochre codons as opposed to the amber codons. Consistent with this hypothesis, addition of an RNA aptamer previously shown to inhibit eRF1/eRF3 (Carnes et al 2000) improved NBD-[ 14 C]Cys incorporation efficiency by twofold at the opal codon and fourfold at the ochre codon (Fig. 4B).…”
Section: Incorporation Of Nbd-labeled Cys Using Cys-derived Suppressosupporting
confidence: 77%
“…The RNA aptamer was generated from synthetic overlapping DNA oligonucleotides encoding aptamer-12 (Carnes et al 2000), T7 promoter, and EcoRI and HindIII sites. The PCR products were ligated into pSP64, and transcription and aptamer purification were performed as for tRNAs.…”
Section: Plasmids and Transcriptionmentioning
confidence: 99%
“…Experiments that address these issues of delivery and persistence in cells may manifest new possibilities for treatment of diseases caused by premature stop codons. We have now shown that, given delivery and persistence, therapeutic oligonucleotide suppression could rely on aptamers (Carnes et al 2000), antisense sequences or RNA interference (this work), or perhaps a more effective combination thereof.…”
Section: Effect Of Sirnas and Antisense Oligonucleotides On Erf1 Protmentioning
confidence: 85%
“…Nevertheless, aminoglycosides are being tested in clinical trials to treat diseases caused by premature stop codons (Wagner et al 2001). Another approach to promote readthrough uses eRF1-binding RNAs, called aptamers, which have been shown to inhibit eRF1 function and affect suppression during translation in vitro (Carnes et al 2000). The efficacy of these eRF1 aptamers, however, has not yet been demonstrated in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…Translation termination factors may serve as a target for the virus. It has been demonstrated that certain isolated RNAs have an affinity for eukaryotic translation termination factors, eRF1, and eRF1⅐eRF3 complexes; to which they not only bind but also inhibit eFR1-mediated release of protein precursor chains from ribosomes (35).…”
Section: Discussionmentioning
confidence: 99%